Mercados, historia y teleología: reflexiones desde la noción de «doble movimiento» de Karl Polanyi - Polo Blanco, Jorge Polo (CONVIVIUM, 2018)
En el presente trabajo mostraremos que la filosofía liberal operó en muchas ocasionesa través de un esquema teleológico, desde el cual entendía que la espontaneidad delmovimiento histórico conducía de forma natural hacia una economía de mercados libres.Semejante interpretación tenía que presuponer otra controvertida tesis, a saber, que lascategorías que informan la racionalidad práctica dentro de una sociedad de mercado no sonuna simple contingencia histórica, sino que responden a la estructura lógica de cualquieracción humana; esto es, como si toda acción humana, en cualquier tiempo y lugar, hubiesefuncionado a través de una misma lógica inmutable que coincidía, en lo esencial, con laracionalidad típica de una economía de mercado. Para adentrarnos críticamente en estaproblemática utilizaremos la obra de Karl Polanyi, cuya obra se oponía frontalmente a estasdos tesis manejadas por el liberalismo económico.
Keywords: MISES, Ludwig von; doble movimiento; double movement; economía de mercado; historical teleology; market economy; teleología histórica

Karl polanyi and the economicist hybris of modernity - Polo Blanco, Jorge (Logos (Spain), 2013)
Using the work of Karl Polanyi as its axis, this study attempts to sketch a criticism of economicism and of the society that produces it, a society launched on a historical cultural path that may well be understood as a gradual economic totalization of human life. That is the critical path which will be posed here, if only in an embryonic manner.
Keywords: economic determinism; economic totalization; economicism

Aristóteles Descubre La Economía, Para Temerla. Una Lectura Desde Karl Polanyi - Polo Blanco, Jorge (ARISTOTLE DISCOVERS ECONOMY, TO FEAR IT. A READING THROUGH THE EYES OF KARL POLANYI., 2017)
This study approaches Aristotelian reflections on economy through the eyes of Karl Polanyi, as he resorts to the Greek philosopher to find useful elements when building a profound criticism of the modern market society. Aristotle intuited the uncertain future of a social order devoured by economic relations expanding at a hypertrophic rate. In his time, indeed, this was only a potential threat —he never saw the effective culmination of anything like what we are seeing today—. But he was nevertheless able to see the ultimate meaning of what was at stake, and to understand that the unmeasured, uncontrolled growth of market relations would irremediably affect civic balance. He understood that the unrestricted extension of the desire for profit to all human ties would be a powerful threat to the heart of the political community. (English)
Keywords: Aristotelian economic philosophy; ECONOMÍA DE LA ANTIGUA POLIS; FILOSOFÍA ECONÓMICA ARISTOTÉLICA; ancient capitalism; capitalismo antiguo; economic of ancient polis; market society; sociedad de mercado